A taxonomic review of Oberthueria Kirby, 1892 (Lepidoptera, Bombycidae: Oberthuerinae) with description of three new species - Zolotuhin, Vadim V.; Wang, Xing (Zootaxa, 2013)
The genus Oberthueria Kirby, 1892 is revised and three new species are described: O. yandu Zolotuhin & Xing Wang, sp. nov. (TL: China, Sichuan, Volong Reserve, Siguliang Shan), O. jiatongae Zolotuhin & Xing Wang, sp. nov. (TL: China, prov. Shaanxi, Taibaishan Mts (S), Tsinling Mts., Foping NT), and O. lunwan Zolotuhin & Xing Wang, sp. nov. (TL: Yunnan prov. (NW), Dali Bai autonom pref., Yulong county).